Digital image multiplexing/demultiplexing method using spatial spectral diffusion and virtual phase conjugation technique for reduction of dynamic range consumption in holographic medium. (23rd August 2017) - Goto, Yuta; Okamoto, Atsushi; Takabayashi, Masanori; Ogawa, Kazuhisa; Tomita, Akihisa
Abstract: The recording density in holographic data storage (HDS) systems is determined by the dynamic range of the recording medium. If a hologram is recorded with a small exposure, the consumption amount of the dynamic range per hologram is reduced, and the recording density can be improved. In this report, we propose a digital image multiplexing/demultiplexing method using spatial spectral diffusion and a virtual phase conjugation technique to reduce the consumption amount of the dynamic range in a recording medium. In our method, multiple signals are simultaneously recorded in a medium by multiplexing those signals using a beam combiner before recording, unlike the general multiplexing method of HDS. Then, each original signal can be reproduced independently by utilizing the property of a random diffuser and a phase-conjugated light. In the simulation, we confirmed that our method can improve the recording density because the consumption of the dynamic range is reduced.